Técnicas de pensamiento lateral para mejorar el rendimiento académico, en diez estudiantes del barrio Daniel Álvarez, de la ciudad de loja, periodo 2020-2021 - Suquilanda Fajardo, Michelle Carolina (2021)
The research work called: Lateral Thinking Techniques to improve academic performance, in ten students from the Daniel Álvarez neighborhood, of the city of Loja, period 2020-2021, had the general objective of formulating Lateral Thinking Techniques to improve performance academic, in ten students from the Daniel Álvarez neighborhood. To carry out the study, a nonexperimental cross-sectional research design was applied and it was framed in the quantitative approach, the scientific, inductive-deductive, analysis and synthesis methods were used, the technique used for the research was a Structured survey and as an instrument the Academic Performance Evaluation Test (TERA) was used, among the main results it was possible to determine that academic performance is a student problem that must be addressed. That is why it is concluded that 80% of the students under study have an unsatisfactory academic performance, based on the dimensions of oral language, written language and mathematical reasoning, so through this research it is recommended to apply the intervention proposal called: "Lateral Thinking Techniques to improve academic performance", to combat the low academic performance presented by students from the Daniel Álvarez neighborhood.